KECAKAPAN LITERASI MEDIA RELIGIUS MUDA DI KONGREGASI OBLAT MARIA IMAKULATA YOGYAKARTA - Rukmono, B. Agus; Borromeus Mulyatno, Carolus; Subali, Y. (Universitas Muhammadiyah Tapanuli Selatan, 2023)
Today, media literacy skills are important to support the tasks, work and services carried out by a religious person. This literacy skill among religious people is important because digital technology can support the works they do, especially those related to evangelism. The purpose of writing this article is to determine the digital media literacy skills of young religious Oblate Maria Immaculate (OMI) Yogyakarta. This study uses a qualitative method with a phenomenological approach. This phenomenological study specifically applies Interpretative Phenomenological Analysis and uses the interview method to obtain data. The results of the research show that young religious in the Congregation of the Oblates of Mary Immaculate already have good digital media skills, especially those related to criticality in filtering information, using the internet to support learning, and using the internet in communicating and networking. This research recommends there is a need for in-depth training so that young religious are not only connoisseurs of the media but are actively involved in contributing various positive activities in the digital world for pastoral purposes. Training is also needed to further strengthen the religious character of young people so they don't easily get immersed in the world of entertainment so that they forget the main things that are their duties and obligations, especially their commitment as a religious.